Influence of heparin-based anticoagulants on antibiotic therapy - Cont, Denisa; Schildböck, Claudia; Kolm, Claudia; Kirschner, Alexander K. T.; Farnleitner, Andreas H.; Hartmann, Jens; Weber, Viktoria; Harm, Stephan (Frontiers in Immunology, 2025)
BackgroundA world without antibiotics is hard to conceive. They have revolutionized the treatment landscape for bacterial infections, reducing mortality rates and enabling complex medical procedures. However, their widespread use has fueled the rise of antimicrobial resistance, a growing global health threat that demands new antibacterial therapies and strategies to preserve the efficacy of existing treatments. Among promising candidates, antimicrobial compounds (AMCs) offer broad-spectrum antimicrobial activity with a lower risk of resistance development. Recent studies suggest that unfractionated heparin, a commonly used anticoagulant, reduces the antibacterial and endotoxin-neutralizing activity of blood-derived AMCs, likely through ionic interactions.MethodsGiven the prevalence of negatively charged anticoagulants in clinical settings, we aimed to explore the effects of unfractionated heparin, low molecular weight heparin, and fondaparinux on the antibacterial activity of AMCs and antibiotics (colistin, daptomycin, gentamicin, imipenem, ofloxacin, and vancomycin).ResultsOur results revealed that both unfractionated and low molecular weight heparin markedly impaired the antibacterial activity of AMCs and positively charged antibiotics, whereas fondaparinux showed no such effect. For instance, exposure to 2.5 IU/mL of unfractionated and low molecular weight heparin led to a significant increase in the minimal inhibitory and minimal bactericidal concentrations of colistin and gentamicin.ConclusionsThese findings support our hypothesis that specific heparin-based anticoagulants interfere with the activity of blood-derived AMCs and positively charged antibiotics, reducing their efficacy in vitro. Our research aims to provide a foundation for future studies focused on optimizing anticoagulant use in clinical settings, ultimately improving patient outcomes in the ongoing fight against multidrug-resistant bacteria.